Selecting a Basal Reading Program: Making the Right Choice - Barnard, Douglas P.; Hetzel, Robert W. (Rowman & Littlefield Publishers, 1989)
This book capitalizes on the authors' longitudinal perspective in program development in approaching a K-12 reading strategy, The school administrator and classroom teacher will find the book's guidelines right to the point. They hit the key issues involved in selecting a reading program: from forming workable and effective professional committees, to conducting the essential evaluations. Anyone who has been through this process will recognize the wealth of expertise required to condense what could be a ponderous and arcane task, into the coherent set of steps and procedures presented in this book. The graphs and tables are invaluable. They will prove enormously helpful in performing each of the tasks in program selections. The authors have set form a process that should enable a school district to optimize the selection and applications of resources in order to maximize pupil learning opportunity. Practitioners will not be disappointed.